Calcineurin inhibitors in the treatment of skin diseases - Silny, Wojciech (Przewodnik Lekarza/Guide for GPs, 2006)
In the period of last 20-30 years, is a new generation of medications – calcineurin inhibitors was introduced. The common trunk of their mechanism is inhibition of immunocompetent cells which are responsible for various inflammatory reactions in humans. These medications are highly immunosuppresive and therefore they are administered in the prophylactics of host immunological reaction in the case of transplants. Soon after their introduction calcineurin inhibitors have been used in the treatment of different inflammatory skin diseases. This paper presents contemporary indications for Cyclosporin A, tacrolimus and pimecrolimus in the treatment of various skin diseases. Some calcineurin inhibitors may be administered systemically while in the case of other medications both systemic and topical types of treatment may be used in dermatology. It has been shown in many clinical trials that Cyclosporin A is highly effective in the treatment of severe atopic dermatitis, psoriasis and other skin diseases. Tacrolimus and pimecrolimus used topically are effective and safe in dermatology. It seems to be important that no systemic side effects are registered during the treatment.